Facilitating Organizational Change to Accommodate an Inpatient Portal - Walker, Daniel M.; Gaughan, Alice; Fareed, Naleef; Moffatt-Bruce, Susan; McAlearney, Ann Scheck (Applied Clinical Informatics, 2019)
Background Patient portals are becoming more commonly used in the hospital inpatient setting. While the potential benefits of inpatient portals are acknowledged, there is a need for research that examines the challenges of portal implementation and the development of best practice approaches for successful implementation.Objective We conducted this study to improve our understanding of the impact of the implementation of an inpatient portal on care team members in the context of a large academic medical center. Our study focused on the perspectives of nursing care team members about the inpatient portal.Methods We interviewed care team members (n = 437) in four phases throughout the 2 years following implementation of an inpatient portal to learn about their ongoing perspectives regarding the inpatient portal and its impact on the organization.Results The perspectives of care team members demonstrated a change in acceptance of the inpatient portal over time in terms of buy-in, positive workflow changes, and acknowledged benefits of the portal for both care team members and patients. There were also changes over time in perspectives of the care team in regards to (1) challenges with new technology, (2) impact of the portal on workflow, and (3) buy-in. Six strategies were identified as important for implementation success: (1) convene a stakeholder group, (2) offer continual portal training, (3) encourage shared responsibility, (4) identify champions, (5) provide provisioning feedback, and (6) support patient use.Conclusion Inpatient portals are recognized as an important tool for both patients and care team members, but the implementation of such a technology can create challenges. Given the perspectives care team members had about the impact of the inpatient portal, our findings suggest implementation requires attention to organizational changes that are needed to accommodate the tool and the development of strategies that can address challenges associated with the portal.
Keywords: patient portals; implementation; organizational culture; hospitalization; nursing informatics; engagement; organizational change